Characterization of 5´ and 3´ UTRs from Bone morphogenetic protein receptor type 1A (Bmpr1A) transcripts under the context of bone metabolism - Silva, Joel Mourato da (2021)
During our life our bones are in a constant balance between bone formation by osteoblasts and bone resorption by osteoclasts. Bone morphogenetic proteins are a group of cytokines from the transforming growth factor-β family involved in several processes. Their signal is transduced through two types of serine/threonine kinase receptors, BMPRI and BMPRII. BMPRIA is a type one receptor involved in osteoblast/osteoclast communication and therefore affecting bone metabolism. Upon binding of different ligands, type II phosphorylates the type I and activates one of the signal pathways. Although their function is known, the mechanisms of regulation of expression are still unclear. The objective of this work was to characterize some of the Mus musculus Bmpr1a molecular regulatory mechanisms including upstream open reading frames (uORFs), polyadenylation sites, microRNA binding sites and constitutive decay elements (CDE). Bioinformatically, we were able to identify 11 Mus musculus Bmpr1a transcripts on available databases, 11 polyadenylations and a constitutive decay element on the 3’UTR, while on 5’UTR we were able to identify 3 uORFs. Experimentally, we isolated a new and shorter Bmpr1a 3’UTR with an alternative polyadenylation site from MC3T3-E1 but without the CDE We tried to isolate different fragments from different tissues, but we were capable of isolate a longer transcript only from mouse liver that contains the CDE loop. Within the 5’UTRs we isolated 4 different fragments containing 2 or 3 uORFs and insert them on reporter plasmids for functional analysis. The last step was mutating all the AUG from uORFs and validating their effect on regulation of luciferase expression. We measured a decrease in the expression of luciferase on fragments containing no mutations and an increase in the expression of fragments with mutations, except in one case where the mutation was inserted 7bp after the start of the fragment. Results indicate that there were no different transcripts from proliferating and differentiated cells, and in the 5’ UTR , the uORFs could possibly contribute to regulate the expression of Bmpr1a. However further studies are needed to confirm and expand our data.